Improvement of autism spectrum disorder symptoms in three children by using gastrin-releasing peptide - Michele Michelin Becker; Cleonice Bosa; Vera Lorentz Oliveira-Freitas; José Roberto Goldim; Lygia Ohlweiler; Rafael Roesler; Gilberto Schwartsmann; Rudimar dos Santos Riesgo (Elsevier, 2016)
Objective: To evaluate the safety, tolerability and potential therapeutic effects of gastrin-releasing peptide in three children with autistic spectrum disorder. Methods: Case series study with the intravenous administration of gastrin-releasing peptide in the dose of 160 pmol/kg for four consecutive days. To evaluate the results, parental impressions the Childhood Autism Rating Scale (CARS) and the Clinical Global Impression (CGI) Scale. Each child underwent a new peptide cycle after two weeks. The children were followed for four weeks after the end of the infusions. Results: The gastrin-releasing peptide was well tolerated and no child had adverse effects. Two children had improved social interaction, with a slight improvement in joint attention and the interaction initiatives. Two showed reduction of stereotypes and improvement in verbal language. One child lost his compulsion to bathe, an effect that lasted two weeks after each infusion cycle. Average reduction in CARS score was 2.8 points. CGI was "minimally better" in two children and "much better" in one. Conclusions: This study suggests that the gastrin-releasing peptide is safe and may be effective in improving key symptoms of autism spectrum disorder, but its results should be interpreted with caution. Controlled clinical trials-randomized, double-blinded, and with more children-are needed to better evaluate the possible therapeutic effects of gastrin-releasing peptide in autism. Resumo: Objetivo: Avaliar a segurança, tolerabilidade e possíveis efeitos terapêuticos do peptídeo liberador de gastrina em três crianças com transtorno do espectro autista. Métodos: Estudo de casuística com administração intravenosa de peptídeo liberador de gastrina na dose de 160 pmol/kg por quatro dias consecutivos. Para avaliar os resultados, foram utilizadas a impressão dos pais, a Escala de Classificação de Autismo na Infância (CARS) e a Escala de Impressão Clínica Global (CGI). Cada criança foi submetida a novo ciclo de peptídeo após duas semanas. As crianças foram acompanhadas por quatro semanas após o término das infusões. Resultados: O peptídeo liberador de gastrina foi bem tolerado e nenhuma criança apresentou efeitos adversos. Duas crianças apresentaram melhora na interação social, com melhora na atenção compartilhada e nas iniciativas de interação. Duas mostraram redução dos estereotipias e melhora na linguagem verbal. Uma criança perdeu sua compulsão por banhos, efeito que durou duas semanas após cada ciclo de infusão. A redução média no escore da CARS foi 2,8 pontos. Quanto à CGI, os resultados foram "minimamente melhor em duas crianças" e "muito melhor" em uma. Conclusões: Este estudo sugere que o peptídeo liberador de gastrina é seguro e pode ser efetivo na melhora dos principais sintomas do transtorno do espectro autista, porém seus resultados devem ser interpretados com cautela. Ensaios clínicos controlados, randomizados, duplo-cego e com maior número de crianças são necessários para melhor avaliar os possíveis efeitos terapêuticos do peptídeo liberador de gastrina sobre o autismo. Keywords: Gastrin-releasing peptide receptor, Neuropeptides, Autism, Autism spectrum disorder, Palavras-chave: Receptor do peptídeo liberador de gastrina, Neuropeptídios, Autismo, Transtorno do espectro autista